2016
DOI: 10.1186/s12879-016-1789-3
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic practices and diarrheal illness among persons living in at-risk settings in Kabul, Afghanistan: a cross-sectional study

Abstract: BackgroundSustained civil and military conflict, resulting in large numbers of internally displaced persons (IDP), in combination with rapid urbanization has strained public health and sanitation within cities in Afghanistan. In order to examine the association between preventive sanitary behaviors and diarrhea within two high risk settings located within Kabul, Afghanistan, this study aimed to evaluate the prevalence of hygienic practices and diarrheal illness in an IDP camp and an urban slum.MethodsIn this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
(20 reference statements)
0
15
2
Order By: Relevance
“…15 As the population has rapidly expanded, the city has faced housing shortages and a decaying sanitary infrastructure. 16,17 Ascariasis was particularly high among those living in hostels, or group homes, and could be explained in part through differences in hygienic behaviors: for instance, students in hostels more commonly consumed well water and unwashed vegetables. Location characteristics have been previously identified as a strong predictors of ascariasis.…”
Section: Discussionmentioning
confidence: 99%
“…15 As the population has rapidly expanded, the city has faced housing shortages and a decaying sanitary infrastructure. 16,17 Ascariasis was particularly high among those living in hostels, or group homes, and could be explained in part through differences in hygienic behaviors: for instance, students in hostels more commonly consumed well water and unwashed vegetables. Location characteristics have been previously identified as a strong predictors of ascariasis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was closely related to a similar study from Addis Ababa which reported 43.89% of the households practice sanitation (Abdissa and Walelegn, 2016). Related finding from Kabul (Afghanistan) showed poor hygienic activities among urban slums (Mubarak et al, 2016). A study from slum of Lucknow, capital of Uttar Pradesh, also reported households had unsafe practices towards water storage and handling (Shukla et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Among the world's regions, Sub-Saharan Africa continue to have the lowest levels of sanitation facility coverage; 44% of the population uses either shared or unimproved facilities (WHO and UNICEF, 2012;WHO and UNICEF, 2013;WHO and UNICEF, 2014). This situation was worse among urban slum dwellers, mainly due to poor sanitation facilities and unhygienic conditions (Erik and Uno, 1994;WHO and UNICEF, 2013;Mubarak et al, 2016). Studies reported the slum environment to be high risk for diarrhoea; due to close proximity of sanitation facilities to homes, sharing of sanitation facilities, and poor hygiene of the sanitation facilities and housing compounds (Mubarak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations